Methodology for diagnosing crack patterns in masonry structures using photogrammetry and distinct element modeling. (15th February 2019) - Napolitano, Rebecca; Glisic, Branko
Highlights: Diagnosing damages on existing infrastructure augments integrity assessment. Photogrammetry and DEM can be combined to diagnose crack patterns in masonry. Fractional distance is a valid metric for comparing simulated and experimental data. Abstract: Understanding the causes of damages on existing structures can augment preservation, renovation, and rehabilitation efforts. The aim of this work is to outline a method for diagnosing the most probable causes of cracks on existing structures using a combination of photogrammetry and distinct element modeling (DEM). Five experimental, masonry walls were constructed and cracked; the state of the wall before and after cracking was recorded using photogrammetry. Using distinct element modeling, each test wall was subjected to a variety of loading conditions including the same load case which was used to crack the wall during experimental testing. The crack patterns in the simulations were compared to the experimental crack patterns using a combined qualitative and quantitative method. The simulation which most closely reflected the existing damage patterns was selected as the most probable cause of the damages. For each of the test walls, the real simulated load had the closest fractional distance to the existing damage patterns captured by photogrammetry. This method was then applied to diagnose possible causes of cracking on a foundation wall in the Baptistery of San Giovani in Florence, Italy.